2001
DOI: 10.1021/om0103963
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Insertion of Isocyanide and Carbon Dioxide into Niobium− and Silicon−Amido Bonds

Abstract: Reaction of the amido-niobium complex [Nb{η 5 -C 5 H 4 SiMe 2 (NH t Bu)}(N t Bu)Cl(NH t Bu)] (2) with 1 equiv of CNAr (Ar ) 2,6-Me 2 C 6 H 3 ) in hexane gave the iminocarbamoyl compound [Nb{η 5 -C 5 H 4 SiMe 2 (NH t Bu)}(N t Bu)Cl{η 2 -C(NH t Bu)dNAr}] (5) in quantitative yield at room temperature, whereas heating to 120 °C was required when similar reactions were carried out with the bridged silyl amido compounds [Nb{η 5 -C 5 H 4 SiMe 2 (η 1 -N t Bu)}(N t Bu)Cl] (3) and 8), which rearranges to the silyl-η 1 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 53 publications
(30 reference statements)
2
27
0
Order By: Relevance
“…For example, the catalyst of diethylzinc with resorcin forms many kinds of oligomers are formed as shown in Eq. (44). All these alternating copolymers formed with this catalyst have a resorcinol group at the terminal position.…”
Section: Aliphatic Polycarbonates and Other Polymersmentioning
confidence: 96%
“…For example, the catalyst of diethylzinc with resorcin forms many kinds of oligomers are formed as shown in Eq. (44). All these alternating copolymers formed with this catalyst have a resorcinol group at the terminal position.…”
Section: Aliphatic Polycarbonates and Other Polymersmentioning
confidence: 96%
“…It has been suggested that aryl-imido ligands provide more crystalline solids [26]. Consequently, we decided to extend our research on Si-Cl functionalized monocyclopentadienyl niobium complexes [11,27,28] to isolate new aryl-imido derivatives using the organomagnesium compounds [Mg(NAr)-(THF)] 6 (Ar = 2,6-Me 2 C 6 H 3 , 1a; Ph, 1b) as imido transfer reagents. This method was first published by Power and co-workers [29] to obtain titanium and zirconium imido compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis of these compounds also led to the isolation of dinuclear derivatives with Si-O-Si bridges for Nb [8,21,25], Mo and W [24] and Si-O-M bridges for Nb [25] and group 4 metals [2,26,27].…”
Section: Introductionmentioning
confidence: 99%